Exploring the practicality of drama activity in teaching English to preschoolers / Nur Ilianis Adnan and Astalakshmi Paranjothi - Adnan, Nur Ilianis; Paranjothi, Astalakshmi (Universiti Teknologi MARA, Pulau Pinang, 2022)
In this study, the main aim is to highlight the importance of drama activity in teaching English to preschoolers. A compilation of literature review of all the relevant papers was done. Generally, children are not born equipped with all the essential knowledge and skills, so, environments that provide new learning opportunities and chances during childhood years are very crucial for the future success of a child. However, encouraging preschoolers to learn English is not an easy task. Using drama is one of the best ways to help preschoolers learn English as the students get the chance to 'play' and have fun while learning. In addition to mastering the language, drama activity also cultivates critical thinking, and this is in line with the Malaysian Education Blueprint 2013-2025. Overall, this new approach is expected to match the learning styles of our Alpha generations in today's modern world. Therefore, it is important for parents, teachers, and policymakers to recognize the benefits of drama activity in educating preschoolers.